1993
DOI: 10.1128/aem.59.10.3183-3186.1993
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial aerosol emission rates from municipal wastewater aeration tanks

Abstract: In this report we describe the results of a study conducted to determine the rates of bacterial aerosol emission from the surfaces of the aeration tanks of the Metropolitan Water Reclamation District of Greater Chicago John E. Egan Water Reclamation Plant. This study was accomplished by conducting test runs in which Andersen six-stage viable samplers were used to collect bacterial aerosol samples inside a walled tower positioned above an aeration tank liquid surface at the John E. Egan Water Reclamation Plant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
2
2
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The upwind sites were located about 100 m upwind of the plants to collect a background (ambient) air sample for bacterial analysis. These samples were used as a check to ensure that no unusually high levels of bacteria were being blown across the sampling area (Sawyer et al 1993). The downwind sites monitored the air flow coming from the treatment locations and were located in a range of 50-100 m from the plants.…”
Section: Samplingmentioning
confidence: 99%
“…The upwind sites were located about 100 m upwind of the plants to collect a background (ambient) air sample for bacterial analysis. These samples were used as a check to ensure that no unusually high levels of bacteria were being blown across the sampling area (Sawyer et al 1993). The downwind sites monitored the air flow coming from the treatment locations and were located in a range of 50-100 m from the plants.…”
Section: Samplingmentioning
confidence: 99%
“…Results supported the use of SBR technology for the removal of indicator organisms and treatment of domestic wastewater. Emissions of total coliforms, fecal coliforms, fecal streptococci, and standard plate count bacteria were measured in aerosols from the aeration basin at a municipal wastewater treatment plant (Sawyer et al, 1993). Two methods, a conventional volumetric method and an empirical method, were used to calculate the bacterial emission rate.…”
Section: Process Microbiologymentioning
confidence: 99%
“…In the case of sanitation-related pathogens -where primary exposure is generally ingestion rather than inhalation -studies in high-risk, extramural (outdoor) settings in the USA and in other highincome countries have revealed that bioaerosols containing enteric microbes are common near point sources of concentrated fecal waste. Studies have primarily focused on ambient air surrounding wastewater treatment plants [32][33][34][35][36][37][38][39][40][41][42][43] and in the context of land application of biosolids [44][45][46][47][48][49][50][51][52][53][54] ; several studies have examined bioaerosols surrounding composting facilities 55,56 , meat markets 57 , impacted urban sites [58][59][60][61][62][63] , and concentrated animal feeding operations [64][65][66] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in high-risk, extramural (outdoor) settings in the USA and in other high-income countries have revealed that bioaerosols containing enteric microbes are common where concentrated fecal waste and one or more mechanisms for aerosolization exist. Enteric microbes in aerosols have been best characterized in ambient air surrounding wastewater treatment plants 2737 and in the context of land application of biosolids 3848 ; several studies have examined bioaerosols surrounding composting facilities 49,50 , meat markets 51 , urban areas 5254 , and concentrated animal feeding operations 5557 . The majority of such studies are based on detection of fecal indicator bacteria including members of the coliform group 54,58 , partly because the presence of important enteric pathogens is unexpected outside high-burden settings.…”
Section: Introductionmentioning
confidence: 99%